Correlation of Family Support with Quality of Life of Patient Chronic Renal Failure Undergo Hemodialysis - Rika Isdiarti; Iwan Ardian (Jurnal Ners, 2020)
Introduction: Family support in patients with chronic renal failure undergoing hemodialysis consists of instrumental support, informational support, emotional support, hope support and self-esteem support. This support is provided throughout the patient's life. The purpose of this research to identify correlation between family support with quality of life of patient chronic renal failure with undergo hemodialysis.Methods: This research was a correlational study. The population was all chronic renal failure patients at one of general hospital in Demak, Central Java, Indonesia, from October to November 2019 as many as 60 patients. This study used total sampling which mean all 60 respondents joined in the study. The instrument is a quality of life questionnaire according to WHOQOL. Data was analyzed with bivariate analysis by using Somer's test with level of significance <0.05.Results: The results showed most of the respondent have family support enough counted 37 respondent (61.7%). Most quality of life of respondent is enough counted 31 respondent (51.7%). Statistical tests performed using Somer’s test show the results of a p-value of 0,000 or significance value of 0,000 <0.05.Conclusion: There is a correlation between family support with quality of life of patients chronic renal failure with hemodialysis. This research can be used as motivation for HD patients and families in improving the quality of life of patients by providing support to improve the patient's life spirit.